2014
DOI: 10.1007/s11947-014-1423-6
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antimicrobial Properties of Biopolymer-Candelilla Wax Emulsion Films Containing Potassium Sorbate – A Comparative Study

Abstract: The comparative studies were performed in order to assess the most suitable matrix polymer for potassium sorbate (KS). The preservative (1.0, 2.0, 3.0, 4.0 % w/w) was included into edible films made from different biopolymers: carboxymethyl cellulose (CMC), oxidized potato starch (OPS), soy protein isolate (SPI), gelatin (GEL), sorbitol, candelilla wax, and emulsifier. The incorporation of KS dramatically reduced the toughness of all tested films. The plasticizing action of KS was the weakest in CMC-based film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…Since the total solid levels in the cast pea starch film remained constant, the addition of glycerol increased the soluble matter present in the films, leading to the formation of structures more sensitive to water (Kowalczyk et al . ). Increasing of water solubility might be because of an increase of the amorphous regions (Flores et al .…”
Section: Resultsmentioning
confidence: 97%
“…Since the total solid levels in the cast pea starch film remained constant, the addition of glycerol increased the soluble matter present in the films, leading to the formation of structures more sensitive to water (Kowalczyk et al . ). Increasing of water solubility might be because of an increase of the amorphous regions (Flores et al .…”
Section: Resultsmentioning
confidence: 97%
“…By incorporation of glycerol, the crystallization development may be partially prevented, because it can disturb the configuration of polymeric chains by interfering with amylose packing through the formation of glycerol–starch and glycerol–water interactions [38]. The increase of glycerol content resulted in weakening the cohesiveness of the polymer structure, creating the polymer network with greater interchain distances [39], thus facilitating more water molecules immobilizing into the pea starch film matrix [40]. The strong tendency of glycerol to water was associated with its high polarity [41].…”
Section: Resultsmentioning
confidence: 99%
“…This result may be attributed to more dissolved state of sorbitol, as a result of increased water content in the AA-added films (Table 1). AA did not prevent sorbitol crystallization in OPS films, most likely due to insufficient moisturizing effect (MC ¼ 8.07e8.74%); previous study (Kowalczyk, Kordowska-Wiater, et al, 2014b) showed that sorbitol did not crystalize from OPS films with MC greater than 10%. It is also possible that inhibition of the plasticizer crystallization in OPS films is difficult, since starch crystals, formed during the retrogradation process, serve as sorbitol-crystal nuclei (Kowalczyk & Baraniak, 2014).…”
Section: Visual Propertiesmentioning
confidence: 65%
“…The plasticizing effect of sorbitol, however, may not be stable during long-term storage. The reason for this is its tendency to recrystallize over time, which could be observed visually from white spots appearing on the film surface (Kowalczyk, Gustaw, et al, 2014a;Kowalczyk, Kordowska-Wiater, Sołowiej, & Baraniak, 2014b). Previous studies have shown that possibility of sorbitol recrystallization depends on both the type of film-forming agent (i.e.…”
Section: Visual Propertiesmentioning
confidence: 99%
See 1 more Smart Citation